Analysis of Teak (Tectona grandis Lf) Chromosome by Staining Method ANALISIS KROMOSOM TANAMAN JATI (Tectona grandis Lf) DENGAN METODE PEWARNAAN - Arum Sekar Wulandari; Tofan Randy Wijaya (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
Counting the number of chromosomes can be conducted by analysis of chromosomes with chromosome staining. The purpose of this research is to find the right method for staining chromosomes of teak, time of the mitotic phase of teak, and the duration of the mitotic phase of teak. Overall, to get good results, chromosomal analysis is done through four stages in the sequence was (1) the early phase of treatment, (2) stage of fixation, (3) stages of maceration and (4) stage of coloration. In this study, there were seven methods of making preparations applied to the root tip mitosis, chromosomes are stained onion root (method A), modification of maceration (method B), modification without fixation and maceration (method C), modifications time to cut teak root (D method), modification of maceration without fixation (method E), the modification of pre-treatment without fixation and maceration (M method), and storage of the root tip before pre-treatments (method G). Chromosome staining onion roots used as a basic for the staining method is easy to get the correct teak’s chromosomes. From this study, analysis of teak’s chromosome is known that D chromosome staining method is appropriate because the methods and stages of mitotic chromosomes can be seen, but the number of chromosomes can not be calculated because the size of chromosomes were very small. the best time to cut the teak root at 9:00 to 10:00 am, and the duration of the mitotic phase of teak is ± 1 hour.Key words : chromosome, chromosome staining method, mitotic, Tectona grandis